Monitoring the Intracellular Distribution and ROS Scavenging Potential of Carbon Dot–Cerium Oxide Nanocomposites in Fibroblast Cells. Issue 3 (2nd February 2016) - Sachdev, Abhay; Gopinath, P.
Abstract: In the present work, cerium oxide (CeO2 )‐based nanocomposites integrating fluorescent carbon dots (CDs) were synthesized by a hydrothermal method. The formation and cellular uptake of these nanocomposites was studied by various analytical techniques. The therapeutic and imaging aspects of CDs‐CeO2 nanocomposites were validated using NIH3T3 fibroblast cells as a model system. The antioxidant potency of CDs‐CeO2 nanocomposites was also evaluated in cells treated with H2 O2, a major reactive oxygen species (ROS) species, using a 2′, 7′‐dichlorofluorescin diacetate (DCFH‐DA) assay. Tracking the intracellular fluorescence of CDs‐CeO2 nanocomposites by microscopy and flow cytometry made it possible to examine the capabilities of CeO2 for abatement of H2 O2 ‐mediated oxidative stress. Taken together, the present study motivates the use of therapeutic nanocomposites whilst monitoring their uptake, which holds clinical relevance for ROS‐related diseases. Abstract : Better together : A facile hydrothermal approach affords multifunctional carbon dot–cerium oxide (CDs‐CeO2 ) nanocomposites with potential applications in imaging and as antioxidants. Fluorescence emission of CDs in nanocomposites serves two key purposes: following their cellular uptake and evaluating the reactive oxygen species (ROS) scavenging activity of CeO2 . These versatile features allow the monitoring and prevention of oxidative stress in cells.